An area-adaptive multi-level layout for social network visualisation. (2016) - Du, Xiaolin; Ye, Yunming; Li, Yueping
We describe an area-adaptive multi-level layout for visualising social networks. This area-adaptive layout can visualise social networks according to the display area and community structure, which could reasonably utilise the display area and enhance the community features. The whole process consists of two parts: graph multi-layered compression and top-down multi-level layout. The multi-layered compression process groups vertices to form clusters and then abstracts the clusters as new vertices to define a new graph and is repeated until the graph size falls below some threshold. Based on the compressed graph, we optimise the display area to top-down positions all vertices. We have evaluated our layout on several well-known data sets. The experimental results show that our layout outperforms the state-of-the-art methods.